2023
DOI: 10.3390/ijerph20021018
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Mindfulness-Based Family Psychoeducation Intervention for the Caregivers of Young Adults with First-Episode Psychosis: A Randomized Controlled Trial

Abstract: Objective: In this study, we investigated the effects of a mindfulness-based family psychoeducation (MBFPE) program on the mental-health outcomes of both caregivers and young adults with first-episode psychosis with an onset in the past three years through a multi-site randomized controlled trial. We also studied the outcomes of three potential mediating effects of interpersonal mindfulness, expressed emotions, and non-attachment on the program. Method: We randomly assigned 65 caregivers of young adults with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 55 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…We are unable to conclusively explain the lack of positive effects on parent-related outcomes in the current study although we speculated that the timing of outcome collection during COVID-19 may have contributed to increased stress among parents over time. A recent study by Zhang et al [ 47 ] conducted during the COVID pandemic found similar findings of no significant improvement on mental health outcomes among caregivers of psychosis patients after receiving CBT.…”
Section: Discussionmentioning
confidence: 71%
“…We are unable to conclusively explain the lack of positive effects on parent-related outcomes in the current study although we speculated that the timing of outcome collection during COVID-19 may have contributed to increased stress among parents over time. A recent study by Zhang et al [ 47 ] conducted during the COVID pandemic found similar findings of no significant improvement on mental health outcomes among caregivers of psychosis patients after receiving CBT.…”
Section: Discussionmentioning
confidence: 71%
“…In this pilot study, the MBP demonstrated some reduction in parenting stress and children’s ADHD symptoms. These results could be explained by a previous study where young adults with psychosis reported significant reductions in their parent’s EE after their parents completed a MBP ( 52 ). This reduction in EE may be a potential mechanism behind the positive changes in MBP for parents.…”
Section: Discussionmentioning
confidence: 78%
“…Prior to the publication of this manuscript, we conducted an updated search to January 2024. As this search identified only four further eligible studies, 64 , 65 , 66 , 67 which would represent an increase of only 10% in our included participants, and would not add any new combinations of components—we felt that their inclusion would be unlikely to result in material changes to our results or conclusions and did not justify repeating our analysis. Finally, although we conducted a methodologically rigorous literature search, we cannot exclude the possibility that we failed to identify relevant published or unpublished studies.…”
Section: Discussionmentioning
confidence: 99%